MONITORING DAYA DUKUNG DAN STATUS MUTU AIR KEGIATAN BUDIDAYA KERAMBA JARING APUNG DI WADUK RIAM KANAN - Rahayu Rahayu; Abdur Rahman; Deddy Dharmaji (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
This study aims to monitor the carrying capacity of the Riam Kanan. Reservoir in the activity of Floating Net Keramba (KJA) based on the content of phosphate (P) and water quality status in Riam Kanan reservoir. The data generated from the measurements are presented in tabulations and diagrams. Data analysis using method of Beveridge(1996) and STORET method according KepMen LH number 115 year 2003 and quality standard according to PP 82 year 2001.The result of research based on water quality status criteria in Riam Kanan reservoir with calculation of water quality status criteria using STORET method at station1, 2 and 3 of total score range from -2 to -8, including class B water quality status that is good criteria of light contamination. Types of fish cultivated in at stations 1 and 2 are tilapia. The results of carrying capacity research using the Beveridge (1996) method in reservoir Riam Kanan for station 1 can be increased the number of units of KJA as much as 54 units and 2 stations 2 as many as 18 units of KJA.